Prediction and bioactivity of small-molecule antimicrobial peptides from Protaetia brevitarsis Lewis larvae - Fu, Qian; Cao, Dengtian; Sun, Jing; Liu, Xinbo; Li, Haitao; Shu, Changlong; Liu, Rongmei (Frontiers in Microbiology, 2023)
Antimicrobial peptides (AMPs) are widely recognized as the promising natural antimicrobial agents. As the largest population of living organisms, insects have great potential as a source of AMPs. It is worthwhile to investigate novel AMPs from Protaetia brevitarsis Lewis larvae which is a saprophagous pest in China. A novel small molecule antimicrobial peptide, designated FD10, has strong bacteriostatic activity against bacteria and fungi. In this research, nine natural AMPs as templates were obtained by comparing with the whole-genome sequence of Protaetia brevitarsis Lewis larvae and the Antimicrobial Peptide Database (APD3). According to the template sequences, 30 truncated sequences were predicted by bioinformatics software analysis of structural characteristics, and then 16 of them were selected as candidate small molecule AMPs to artificially synthesize through the analysis of physicochemical properties. The preliminary studies of biological activities showed that five candidate peptides had antimicrobial activity. After that, analysis of the minimal inhibitory concentration (MIC) demonstrated that a candidate peptide designated FD10 exhibited strong antimicrobial activity against both bacteria and fungi including Escherichia coli (E. coli 8 μg/mL), Pseudomonas aeruginosa (8 μg/mL), Bacillus thuringiensis (8 μg/mL), Staphylococcus aureus (S. aureus 16 μg/mL) and Candida albicans (16 μg/mL). Besides that, the other two candidate peptides designated FD12 and FD15 exhibited antimicrobial activity against both E. coli (32 μg/mL;32 μg/mL) and S. aureus (16 μg/mL;16 μg/mL). In addition, FD10, FD12, and FD15 killed over 99% of E. coli and S. aureus within 1 h, and the hemolysis of FD10 (0.31%) and FD12 (0.40%) are lower than ampicillin (0.52%). These results indicate that FD12, FD15, and especially FD10 have the potential to become novel antimicrobial agents and provide a basis for the study of novel antibiotics.